Kewenangan Menguji Peraturan Perundang-Undangan dalam Sistem Ketatanegaraan Indonesia menurut Undang-Undang Dasar Negara Republik Indonesia Tahun 1945 - Yohanes Baptista Geroda Laga Doni Soge; Saryono Yohanes; Mario Aprio Almit Lawung; Rafael Rape Tupen (Pusat Riset dan Inovasi Nasional, 2026)
This study aims to analyze the regulation and implementation of the authority to test laws and regulations (judicial review) in the Indonesian state system based on the 1945 Constitution of the Republic of Indonesia. This study applies a normative juridical method using three main approaches, namely the statute approach, the conceptual approach, and the historical approach. The legal data collected includes primary, secondary, and tertiary legal materials, which are then reviewed through qualitative analysis. The results of the study show that normatively the division of judicial review authority between the Supreme Court and the Constitutional Court has been expressly regulated in Article 24A paragraph (1) and Article 24C paragraph (1) of the 1945 Constitution of the Republic of Indonesia. The Supreme Court is given the authority to test regulations under the law against the law, and the Constitutional Court is given the authority to test laws against the 1945 Constitution. This division of authority is a manifestation of the principle of separation of powers and the mechanism of checks and balances after the third amendment to the 1945 Constitution. However, in practice, this two-roof judicial review system tends to give rise to conceptual and practical problems, such as overlapping authority and differences in decisions between the Supreme Court and the Constitutional Court which have the potential to create legal uncertainty and reduce public trust in the judicial institution. Therefore, it is necessary to reorganize the authority of judicial review by strengthening coordination between institutions or unifying the authority of judicial review which is centered on one institution only in order to guarantee legal certainty, harmonization of norms, and supremacy of the constitution in the Indonesian state system.